Running Wild - Dolar, Mladen (Stasis, 2016)
The paper takes its cue from Freud’s short text “Observations on ‘Wild’ Psychoanalysis” (1910), where Freud considers the advice that presents sex as the universal cure for anxiety and ultimately all psychic troubles. The advice, dispensed by a non-analyst but also circulating in general opinion, is presented as supported by the psychoanalytic scientific discovery. The paper follows Freud’s steps arguing that sex is not an entity that can be located, but rather resides in a dislocation; that it doesn’t have predictable effects that would follow the path of somatic causality; that sexual satisfaction is not the cure for neurotic disorders; that one has to take into account the specificity of the Freudian notion of the unconscious; that sex is neither a fact nor a cause, but nevertheless produces effects. Freud’s argument is pitted against the Anti-Sexus machine, presented by Platonov as a device that rests on the mistaken assumptions about the sexuality Freud was fighting against.